2008
DOI: 10.1007/s12038-008-0056-1
|View full text |Cite
|
Sign up to set email alerts
|

The polymorphisms of bovine cocaine-and amphetamine-regulated transcripts and their associations with cattle (Bos taurus) growth traits

Abstract: We investigated the polymorphisms of bovine cocaine- and amphetamine-regulated transcripts (CART ). The coding and regulating regions of CART were screened in 7 cattle breeds by the single-stranded conformation polymorphism (SSCP) technique. The four loci (C1,C2, C3 and C4) studied were all polymorphic. Polymerase chain reaction (PCR) products representing different SSCP variants were sequenced and a total of 9 single-nucleotide polymorphisms (SNPs) were found. The associations between polymorphic loci and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…In humans, the missense mutation Leu 34 Phe may lead to obesity (Yanik et al, 2006). Reports in cattle showed that some single nucleotide polymorphisms (SNPs) (-636T→C, -521T→C, -1431T→C, -398T→C, and 234A→G) were associated with growth traits (Zhang et al, 2008). Findings in pigs demonstrated that swine with (CA) 2 (CG) 1 (CA) 9 or (CA) 2 (CG) 3 (CA) 11 had significant effects on meat content carcass (P < 0.05) in both Polish Large White and Polish Landrace breeds (Stachowiak et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In humans, the missense mutation Leu 34 Phe may lead to obesity (Yanik et al, 2006). Reports in cattle showed that some single nucleotide polymorphisms (SNPs) (-636T→C, -521T→C, -1431T→C, -398T→C, and 234A→G) were associated with growth traits (Zhang et al, 2008). Findings in pigs demonstrated that swine with (CA) 2 (CG) 1 (CA) 9 or (CA) 2 (CG) 3 (CA) 11 had significant effects on meat content carcass (P < 0.05) in both Polish Large White and Polish Landrace breeds (Stachowiak et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Some of them refer to humans (Kasacka and Piotrowska 2012;Banke et al 2013). There are few sources available dealing with the CART activity in cattle, and the majority of articles mostly discuss CART location in the stomach and the nervous system (Kobayashi et al 2006;Zhang et al 2008;Arciszewski et al 2009;Smithet al 2010;Janiuk et al 2013). Until now, no studies have been performed to analyse the relationship between CART and functional traits of the organism.…”
mentioning
confidence: 99%
“…The current knowledge of CART incidence in ruminants is incomplete, since it only refers to sheep and cattle (Zhang et al 2008;Arciszewski et al 2009). In the case of bovine studies performed inthe last years are fragmentary and concern the expression of this neuropeptide in the centers nerves system in different cattle breeds (Zhang et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of bovine studies performed inthe last years are fragmentary and concern the expression of this neuropeptide in the centers nerves system in different cattle breeds (Zhang et al 2008). The results of these authors have shown a relationship between the amount of secreted CART and the daily body weight gains of the animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation